Chaetomitrium Philippinense - Monica Suleiman; Hiroyuki Akiyama (2014)
(1) Plants are robust and branches are cuspidate and homomallous; (2) branch leaves apices are often twisted and strongly constricted; (3) leaf margins are denticulate above with geminate teeth; (4) lamina cells are prorate.